Factors Affecting Prevention Behavior against Thirdhand Smoke (THS)Exposure: Systematic Literature Review - Aldyta Permata Sari; Nur Rohmah; Annisa Nurrachmawati (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Thirdhand smoke (THS) is tobacco residue left on surfaces and dust after cigarette smoke disappears, which can increase health risks, especially for children. Understanding the factors that influence THS prevention behavior is essential for the development of effective public health interventions. This study aimed to identify and synthesize various factors that influence THS exposure prevention behavior through a SLR. Articles were systematically searched on PubMed, Google Scholar, and Scopus for publications from 2021 to 2025, referring to the 2020 PRISMA guidelines and strict into inclusion-exclusion criteria. Of the 280 articles identified, 12 studies (total 5,241 participants) were included, the majority of which were cross-sectional in design and predominantly from Turkey. The main factors influencing THS prevention behavior included: awareness and knowledge (10 studies), belief about the dangers of THS (8 studies), education (6 studies), income (5 studies), smoking rules at home (5 studies), and smoking behavior (4 studies). Awareness of the term THS was still low (8.7%). Higher education (OR=18.835; p<0.001) and home ownership (OR=2.667; p=0.004) significantly influenced beliefs about the dangers of THS. Information about nicotine levels on children's hands increased parents' concerns and intentions to improve. In conclusion, awareness, knowledge, belief in the dangers of THS, and sociodemographic factors are the main determinants of THS prevention behavior. Public health interventions need to target THS education at low-income and low-education groups. Further research is needed in diverse contexts.